THE BLOCK 36 - TOUTIN, Thierry (MEDECINE LEGALE DROIT MEDICAL, 2025)
The block 36 of the psychiatric hospital «Maison-Blanche» in Neuilly sur Marne (France) is the place where a series of murders took place on the night of May 4 to 5, 1979. at night, a 37-year-old man, who had not been searched, had just been admitted to the hospital with a concealed knife on his person. During the night, in a state of delirious madness, he will carry out a series of homicides, killing five patients located in the same dormitory. A sixth patient later died of his injuries. Forty-four years later, the author of this article who learned of this terrible night, while he was a trainee police inspector at the Neuilly sur Marne police station, asks himself the question: Could this rather rare tragedy have been avoided? It seems not at the time, if we take into account the fragmentary elements later collected about this case